SUSTAINABLE SOIL FERTILITY MANAGEMENT FOR OPTIMUM CROP PRODUCTION - Adediran , J. A.; Banjoko , V. A.; Taiwo , L. B.; Idowu , O. J.; Oluwatosin , G. A.; Akande , M. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Declining agricultural productivity in Nigeria is a consequence of general mismanagement of the soils. A large area of agricultural land has been damaged and rendered unproductive due to poor soil management practices. Sustenance of soil management in the country therefore entails wise use and maximization of soil resources for optimum soil and crop productivity. Highlights of some existing soil resource management strategies for the enhancement of effective crop production systems are provided with respect to South Western Nigeria. Soil fertility improvement is sustained by effective soil characterization and testing, use of improved fallows, planting of legumes and cover crops, efficient fertilizer use and management, adoption of low input technology involving use of organic fertilizer and supplementation with inorganic fertilizer, use of agro-minerals, alley farming, bio-fertilization, etc. In other to avoid rapid degradation of soils, appropriate methods, which serve to prevent erosion and compaction, are used. These methods include surface mulching, use of minimum tillage for mechanically cultivated land and incorporating appropriate cover and fallow crops in the farming system. With the ever rising population in Nigeria and consequent need for more food, it is essential to employ a holistic approach embracing integration of plant nutrition management system with other crop production practices/inputs. This approach enhances sustainable soil fertility management for optimum crop production in the country.